2017
DOI: 10.4314/tjpr.v16i4.21
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of aqueous myrrh extract alone and in combination with cisplatin in HeLa cells

Abstract: Purpose: To study the impact of an aqueous myrrh extract on the proliferation of cervical cancer cells in vitro.Methods: First, 100 g of ground myrrh resin was boiled in 1000 mL of distilled water for 30 min. Different components of the decoction were identified using gas chromatography-mass spectrometry and high-performance liquid chromatography. The effects of high (20 µg/mL) and low (10 µg/mL) concentrations of cisplatin, serial concentrations of myrrh (20, 40, 60, and 80 µg/mL), and a combination of both w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Furthermore, Myrrh has antipyretic, analgesic, and antiseptic activities (Shalaby and Hammouda 2014) antirheumatic (Su et al, 2015), antiparasitic (El-Sayad et al, 2017), hypotensive (Abdul-Ghani and Amin 1997), antimicrobial (Mahboubi and Mohammad, 2016), and a strong antifungal activity (Perveen et al, 2018). Many studies confirmed in vitro the cytotoxic activity of Myrrh on human tumor cell lines especially HCC and induce a high level of apoptosis (Ramadan et al, 2017;Khalil et al, 2020) while in vivo, it reduces the rate of tumor growth (Mahmoud et al, 2017). Consequently, this study was conducted to assess the hepatoprotective effect of C. molmol resin water extract against DEN-induced early-stage hepatocarcinogenesis in male albino rats via its modulator role on tumor markers as AFP, TNF-α, CEA, Angiogenic factors, apoptosis, oxidative stress as well as histopathological alterations.…”
Section: Research Articlementioning
confidence: 97%
“…Furthermore, Myrrh has antipyretic, analgesic, and antiseptic activities (Shalaby and Hammouda 2014) antirheumatic (Su et al, 2015), antiparasitic (El-Sayad et al, 2017), hypotensive (Abdul-Ghani and Amin 1997), antimicrobial (Mahboubi and Mohammad, 2016), and a strong antifungal activity (Perveen et al, 2018). Many studies confirmed in vitro the cytotoxic activity of Myrrh on human tumor cell lines especially HCC and induce a high level of apoptosis (Ramadan et al, 2017;Khalil et al, 2020) while in vivo, it reduces the rate of tumor growth (Mahmoud et al, 2017). Consequently, this study was conducted to assess the hepatoprotective effect of C. molmol resin water extract against DEN-induced early-stage hepatocarcinogenesis in male albino rats via its modulator role on tumor markers as AFP, TNF-α, CEA, Angiogenic factors, apoptosis, oxidative stress as well as histopathological alterations.…”
Section: Research Articlementioning
confidence: 97%
“…It is estimated that the 5-year survival rate in cervical carcinoma patients with lymphatic metastasis is only 50.8 % [5]. Although the screening method of cervical carcinoma has been widely popularized, the 5-year survival rate is not good [2,5,6]. Surgery, chemotherapy and radiotherapy are the major therapeutic strategies for cervical carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Annually, approximately 530,000 people die of cervical carcinoma worldwide [1,2], and up to 460,000 new diagnoses of cervical carcinoma are recorded every year globally, with about 50 % of them from Asia [2][3][4]. Potential pathogenic Trop J Pharm Res, June 2022; 21 (6): 1148 factors for cervical carcinoma include premature sexual activity, sexual life disorder, premature birth, multiparous births, racial and geographical causes, poor economy, human papillomavirus (HPV) infection, etc. In particular, HPV infection is a major reason for the carcinogenesis of cervical carcinoma [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major output of this study was that verjuice extract could suppress A549 cells' viability where minor concentrations of this extract could strongly enhance cisplatin's anticancer potential. In this context, various studies have previously reported the importance of the combination of cisplatin and plant-derived natural molecules to increase the anticancer potential of cisplatin [31,32]. Moreover, administration of verjuice was shown to reduce atherosclerotic and fibrinogen lesions in coronary arteries of rabbits [33].…”
Section: Co-treatment With Cisplatin and Verjuice Has Superior Inhibitory Effects On A549 Cell Viabilitymentioning
confidence: 99%